Najpogostejše kršitve delovne zakonodaje - Rakita, Jasmina (Delavci in delodajalci, 2017)
The purpose of this presentation is to outline the most frequent detected violations within labour relation legislation in 2016 and to present imposed measures by underlining the recorded abuses within the area of prohibition on the conclusions of civil law contracts that are contravention to the current legal regulations. The result of the surveillance role of the Labour Inspectorate is presented as well as some other activities in the field of labour relations.
Keywords: delodajalci; delovno pravo; inšpekcijski nadzor; kršenje; zaposleni